2004
DOI: 10.4028/www.scientific.net/msf.457-460.35
|View full text |Cite
|
Sign up to set email alerts
|

Development of Large Diameter High-Purity Semi-Insulating 4H-SiC Wafers for Microwave Devices

Abstract: The next generation of wireless infrastructure will rely heavily upon wide band gap semiconductors owing to their unique materials properties, including: their large bandgap, high thermal conductivity, and high breakdown field. To facilitate implementation of this next generation, a significant effort is required to make SiC MESFET and GaN HEMT microwave devices more suitable for widespread application. Currently, the interest in high-purity semiinsulating (HPSI) 4H-SiC is critically tied to its influence on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 14 publications
(12 reference statements)
0
37
0
Order By: Relevance
“…More recently, use of intrinsic point defects, which create deep levels, has been investigated, and "highpurity semi-insulating" (HPSI) wafers have been obtained [76,77]. Intrinsic point defects can be introduced by adjusting the growth conditions or by high-energy particle irradiation after growth [78].…”
Section: Doping Controlmentioning
confidence: 99%
“…More recently, use of intrinsic point defects, which create deep levels, has been investigated, and "highpurity semi-insulating" (HPSI) wafers have been obtained [76,77]. Intrinsic point defects can be introduced by adjusting the growth conditions or by high-energy particle irradiation after growth [78].…”
Section: Doping Controlmentioning
confidence: 99%
“…In the high-purity semiinsulating (HPSI) SiC materials grown by high-temperature chemical vapor deposition (HTCVD) [10,11] and PVT [12,13], the compensation of shallow donor and acceptor levels was achieved by intrinsic deep-level defects. However, the exact nature of the intrinsic defects involved in the compensation mechanisms is still under investigation [5,17].…”
Section: Introductionmentioning
confidence: 99%
“…Main approaches to achieving SI properties in SiC include (1) intentional vanadium (V) doping [3][4][5][6][7] and (2) use of deep levels caused by intrinsic defects [8][9][10][11][12][13]. Other transition metals such as iron (Fe) have also been investigated for producing resistive SiC substrates and epitaxial layers [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In HPSI SiC substrates grown by hightemperature chemical vapor deposition ͑HTCVD͒ ͑Refs. 4-6͒ or by physical vapor deposition 7,8 semi-insulating ͑SI͒ properties have been achieved using intrinsic defects. In those materials, deep acceptor levels of vacancy-related defects can compensate the residual N shallow donors to pin the Fermi level to one of the deep levels and highly resistive materials with typical resistivity in the range of 10 6 -10 10 ⍀ cm can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…In those materials, deep acceptor levels of vacancy-related defects can compensate the residual N shallow donors to pin the Fermi level to one of the deep levels and highly resistive materials with typical resistivity in the range of 10 6 -10 10 ⍀ cm can be achieved. [4][5][6][7][8] There are different types of HPSI SiC materials characterized by different activation energies ranging from ϳ0.6 to ϳ1.6 eV. [4][5][6][7][8] It has been shown that carrier compensation processes in HPSI 4H-SiC materials are complicated, involving different defects of which the silicon vacancy ͑V Si ͒, the carbon vacancy ͑V C ͒, the carbon antisite-vacancy pairs ͑C Si V C ͒, and the divacancy ͑V C V Si ͒ are the most prominent ones.…”
Section: Introductionmentioning
confidence: 99%